Conditional Correctness of a BoundaryBorder Problem for a System of TimeVarying Directional Equations - Khajiyev I.O; Mamatkulova M.Sh.; Rozimatov J.A. (Global Scientific Publishing, 2023)
In this work, the initial-boundary ill-posed problem for the system of timevarying parabolic equations, which depend on each other, is studied. In this case, an a priori estimate of the solution of the problem is obtained, and the theorems of uniqueness and conditional stability of the solution are proved in the correctness set
Keywords: incorrect problem; a priori estimate; correctness set; conditional stationarity theorem